Patients with alcohol-related liver disease hospitalized during the COVID-19 pandemic experienced worse outcomes - Lindsay A Sobotka; Ayushi Jain; Jing Peng; Kenneth D Allen; Chelsey J McShane; Mitchell L Ramsey; Michael R Wellner; Robert B Kirkpatrick (Annals of Hepatology, 2023)
Introduction and Objectives: Psychosocial stressors related to the coronavirus-19 (COVID-19) pandemic increased alcohol consumption. The effect on patients with alcohol-related liver diseases remains unclear. Materials and Methods: Hospitalizations at a tertiary care center due to alcohol-related liver disease from March 1 through August 31 in 2019 (pre-pandemic cohort) and 2020 (pandemic cohort) were reviewed retrospectively. Differences in patient demographics, disease features, and outcomes were estimated in patients with alcoholic hepatitis utilizing T-tests, Mann-Whitney tests, Chi-square and Fisher Exact Tests and Anova models and logistic regression models in patients with alcoholic cirrhosis. Results: 146 patients with alcoholic hepatitis and 305 patients with alcoholic cirrhosis were admitted during the pandemic compared to 75 and 396 in the pre-pandemic cohort. Despite similar median Maddrey Scores (41.20 vs. 37.45, p=0.57), patients were 25% less likely to receive steroids during the pandemic. Patients with alcoholic hepatitis admitted during the pandemic were more likely to have hepatic encephalopathy (0.13; 95% CI:0.01, 0.25), variceal hemorrhage (0.14; 95% CI:0.04, 0.25), require oxygen (0.11; 95% CI:0.01, 0.21), vasopressors (OR:3.49; 95% CI:1.27, 12.01) and hemodialysis (OR:3.70; 95% CI:1.22, 15.13). On average, patients with alcoholic cirrhosis had MELD-Na scores 3.77 points higher (95% CI:1.05, 13.46) as compared to the pre-pandemic and had higher odds of experiencing hepatic encephalopathy (OR:1.34; 95% CI:1.04, 1.73), spontaneous bacterial peritonitis (OR:1.88; 95% CI:1.03, 3.43), ascites (OR:1.40, 95% CI:1.10, 1.79), vasopressors (OR:1.68, 95% CI:1.14, 2.46) or inpatient mortality (OR:2.00, 95% CI:1.33, 2.99) than the pre-pandemic. Conclusions: Patients with alcohol-related liver disease experienced worse outcomes during the pandemic.